Bibliometric analysis of research on gene expression in spinal cord injury - Wang, Siqiao; Qian, Weijin; Chen, Shaofeng; Xian, Shuyuan; Jin, Minghao; Liu, Yifan; Zhang, Hao; Qin, Hengwei; Zhang, Xinkun; Zhu, Jiwen; Yue, Xi; Shi, Chaofeng; et al. (Frontiers in Molecular Neuroscience, 2022)
Background: Spinal cord injury (SCI) is a severe disease with motor and sensory function being destroyed, which leads to a poor prognosis and a great financial burden. It is urgent to figure out the molecular and pathological mechanisms of SCI to develop feasible therapeutic strategies. This article aims to review documents focused on gene expression in SCI and summarize research hotspots and the development process of this field. Methods: Publications of SCI-related studies from 2000 to 2022 were retrieved from the Web of Science Core Collection database. Biblioshiny was used to evaluate the research performance, core authors, journals and contributed countries, together with trend topics, hotspots in the field, and keyword co-occurrence analysis. Visualized images were produced to help comprehension. Results: Among 351 documents, it was found that the number of annual publications increased in general. The most productive country was China, followed by the USA with the highest influence and the most international cooperation. Plos One was the journal with the maximum publications, while Journal of Neuroscience was the most influential one. According to keyword co-occurrence and trend topics analysis, these articles mainly focused on molecular and pathological mechanisms as well as novel therapies for SCI. Neuropathic pain, axonal regeneration and messenger RNA are important and promising research areas. Conclusion: As the first bibliometric study focused on gene expression in SCI, we demonstrated the evolution of the field and provided future research directions like mechanisms and treatments of SCI with great innovativeness and clinical value. Further studies are recommended to develop more viable therapeutic methods for SCI.